2016
DOI: 10.1021/acsami.6b09365
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Nanometric Polydiacetylenic Micelles Allow for Efficient Intracellular siRNA Delivery

Abstract: A novel generation of pH-responsive photopolymerized diacetylenic amphiphile (PDA) micelles with a diameter of 10 nm was designed and optimized for the intracellular delivery of siRNAs. Dialysis and photopolymerization of the micelles allowed a strong reduction of the cytotoxicity of the nanovector, while the hydrophilic histidine headgroup permitted enhancing the siRNA delivery potential by improving the endosomal escape via imidazole protonation. These PDA-micellar systems were fully characterized by DLS, TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 25 publications
(37 reference statements)
1
35
0
Order By: Relevance
“…For the headgroup, we focused on 3 three amino acids, namely histidine (His), tryptophan (Trp) and tyrosine (Tyr). The first amino acid was selected based on our previous results with His-PDA-micelles [10], while Trp was chosen due to its capacity to interact with membranes. [18] Lastly, Tyr was used as it was previously reported that coupling of this amino acid onto the cationic polymer PEI results in an efficient siRNA delivery vector.…”
Section: Synthesis Of the Amphiphilesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the headgroup, we focused on 3 three amino acids, namely histidine (His), tryptophan (Trp) and tyrosine (Tyr). The first amino acid was selected based on our previous results with His-PDA-micelles [10], while Trp was chosen due to its capacity to interact with membranes. [18] Lastly, Tyr was used as it was previously reported that coupling of this amino acid onto the cationic polymer PEI results in an efficient siRNA delivery vector.…”
Section: Synthesis Of the Amphiphilesmentioning
confidence: 99%
“…[9] With these PDA-micelles, we found that when the cationic headgroup was a histidine residue, we obtained vehicles that promote delivery of siRNA molecules into the cytoplasm of cells. [10] The good efficiency of the system is probably based on the fact that the imidazole group of His promotes release of the nucleic acid from the endosomal compartment through a proton sponge mechanism. [11][12][13] This was supported by the fact that inhibition of endosomal acidification severely reduced the silencing efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The last generation of PDA-micelles stabilized by UVphotopolymerization, are self-organized objects in the size range of 10 nm, containing a histidine head group (Hist-PMs, Scheme 1). The micelles allowed for a 90% silencing of a reporter gene using 10 nM siRNA concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The micelles allowed for a 90% silencing of a reporter gene using 10 nM siRNA concentration. 10 In parallel, E. Doris and H. Tian's groups demonstrated the potential of polydiacetylene nanocarriers for antitumoral drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Fore xample, recently,p olymerized polydiacetylenes have been reported for imaging and drug delivery and they demonstrated ahigher stability and drug loading than an on-polymerized counterpart or liposomes. [10] In this work, we present an ovel diacetylene-derived peptide gemini amphiphile (DA 2 P)and investigate its supramolecular self-assembly.InDA 2 P,ahydrophilic arginine and lysine rich pentapeptide (RKARK) is attached through aCterminal glutamic acid to two hydrophobic diacetylene chains (Scheme 1). Thei dea was that the combination of ac ationic pentapeptide related to other,but normally much larger,cellpenetrating peptides with two long hydrophobic diacetylene chains should enhance the interaction of this amphiphile with the negatively charged cell membrane and might lead to more efficient cell uptake.Furthermore,the diacetylene part might undergo fluorescent changes in this process,w hich could be used for sensing or cell imaging.I nterestingly,w ef ound that DA 2 P self-assembled in ac oncentration-dependent manner first into tadpole-and bola-shaped nanostructures (low concentration) and then nanofibers (high concentration).…”
mentioning
confidence: 99%